The Application of SUDOSCAN for Screening Diabetic Peripheral Neuropathy in Chinese Population - Jin, Jiewen; Wang, Weimin; Gu, Tianwei; Chen, Wei; Lu, Jing; Bi, Yan; Zhu, Dalong (Experimental and Clinical Endocrinology & Diabetes, 2018)
Purpose Diabetic peripheral neuropathies are the common chronic complications of diabetes, but the diagnosis is insensitive by physical examination in busy outpatients. Here we evaluated the performance of SUDOSCAN in screening diabetic peripheral neuropathies in Chinese type 2 diabetic patients.Methods The study enrolled 180 patients for annually screening. All patients underwent neurological symptoms assessment, clinical examination, nerve conduction studies and cardiovascular autonomic reflex tests. SUDOSCAN was tested and evaluated with electrochemical skin conductance in hands and feet, asymmetry ratio in hands and feet and predicted cardiac neuropathy.Results Patients enrolled had an average age of 56.1 years, 9.8 years of diabetic duration. Patients with diabetic sensorimotor polyneuropathy showed significantly lower electrochemical skin conductance in feet and higher asymmetry ratio in feet compared with those without. Sensitivity and specificity of asymmetry ratio in feet for diagnosing diabetic sensorimotor polyneuropathy were 88.2% and 46.9% and area under ROC curve was 0.713. Patients with cardiovascular autonomic neuropathy showed significantly lower electrochemical skin conductance in hands and feet, and higher asymmetry ratio in feet and predicted cardiac neuropathy compared with those without. Sensitivity and specificity of electrochemical skin conductance in feet in diagnosing cardiovascular autonomic neuropathy were 85.6% and 76.1% with an area under ROC curve of 0.859.Conclusions SUDOSCAN is a sensitive test to detect diabetic peripheral neuropathy in China and could be an effective screening tool in in busy outpatients and primary health care.
Keywords: cardiovascular autonomic neuropathy; diabetic sensorimotor polyneuropathy; SUDOSCAN; type 2 diabetes; Chinese population